Effect Of Local İnjection Of Parathyroid Hormone On Orthodontic Tooth Movement İn Rats - M. Cem Caniklioğlu; Yıldız Kırlıç; Vakur Olgaç (Galenos Yayinevi, 1999)
The aim of this study is to evaluate the effect of different doses and the numbers of injections parathyroid hormone on the rate of tooth movement, alveolar bone and on Ca and P levels in blood. Fifteen male sprague dawley rats 220±10 gr. in weight and 90 days of age were used in this study. Orthodontic appliance were inserted on the upper first molar and different doses and numbers of parathyroid hormone were injected Tooth movement is measured on radiographs taken at the beginning and at the end of the experiment. All animals were killed at 14 th. day of the experiment. The heads were dissected and processed for histological examination, blood serum was tested for the level of Ca and P. The fastest tooth movement occurred after local injection of 17 pgr. of parathyroid hormone 3 times. There was no difference in blood Ca and P levels between control and experimental animals. Histologically .there was no pathological changes on alveolar bone due to the local injection of parathyroid hormone.